Eat right! 2005 food pyramid - Learning seed (Lake Zurich, Ill. : Learning Seed, 2006)
The 2005 version of the guidelines and food pyramid emphasize the importance of physical activity and eating nutrient dense foods
Keywords: Nutrition -- Requirements; Diet -- United States; Health education